2006
DOI: 10.1111/j.1471-0528.2006.00886.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of intrapartum automated fetal electrocardiography and conventional cardiotocography—a randomised controlled study

Abstract: Objective To examine whether intrapartum monitoring by means of automatic ST analysis (STAN) of fetal electrocardiography could reduce the rate of neonatal acidemia and the rate of operative intervention during labour, compared with monitoring by means of cardiotocography (CTG).Design Randomised controlled trial.Setting Labour ward in tertiary-level university hospital.Sample A total of 1483 women in active labour with singleton term fetus in cephalic presentation.Methods Women were randomly assigned to be mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
4
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(128 citation statements)
references
References 8 publications
3
113
4
7
Order By: Relevance
“…334 With this technique, T-wave amplitude was noted to be increased during states of asphyxia; these changes were believed to be attributable to myocardial potassium liberation during glycolysis. 335 Results of several randomized, clinical trials using fetal electrocardiography involving >15 000 patients after 36 weeks' gestation [336][337][338] have shown variable results in the outcome measures of reduction in metabolic acidosis, decrease in moderate/severe neonatal encephalopathy, and operative delivery rate. Although the use of fetal electrocardiography may be reasonable to consider in the assessment of cardiac conduction and rhythm in fetuses with known or suspected diseases of the conduction system, its utility has not been established.…”
Section: Fetal Electrocardiographymentioning
confidence: 99%
“…334 With this technique, T-wave amplitude was noted to be increased during states of asphyxia; these changes were believed to be attributable to myocardial potassium liberation during glycolysis. 335 Results of several randomized, clinical trials using fetal electrocardiography involving >15 000 patients after 36 weeks' gestation [336][337][338] have shown variable results in the outcome measures of reduction in metabolic acidosis, decrease in moderate/severe neonatal encephalopathy, and operative delivery rate. Although the use of fetal electrocardiography may be reasonable to consider in the assessment of cardiac conduction and rhythm in fetuses with known or suspected diseases of the conduction system, its utility has not been established.…”
Section: Fetal Electrocardiographymentioning
confidence: 99%
“…Although our findings differ from those of two randomized trials, 8,9 they are in agreement with those of other randomized trials. [17][18][19] Our findings of no improvement in neonatal outcomes or reduction in cesarean-delivery rates are also consistent with the results of a meta-analysis of individual-patient data from ST-segment analysis trials, 20 which showed that electronic fetal monitoring with adjunctive ST-segment analysis, as compared with conventional electronic fetal monitoring alone, did not reduce the rates of neonatal metabolic acidosis, need for intubation, hypoxic-ischemic encephalopathy, a composite neonatal outcome, or cesarean delivery. 20 However, that meta-analysis showed a reduction in the frequency of fetal blood sampling (which is not routine in the United States) and operative vaginal delivery among women who underwent electronic fetal monitoring and adjunctive ST-segment analysis, as compared with those who underwent electronic fetal monitoring alone.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Complementary methods, such as fetal scalp pH and lactates, fetal electrocardiogram (ECG) ST segment analysis, and T/QRS ratio (STAN 1 ; Neoventa Medical, Moelndal, Sweden), have been shown, at the best, to modestly reduce fetal metabolic acidosis and rate of operative deliveries. [3][4][5][6] As FHR with reduced or absent variability is one of the most significant parameters to predict the development of fetal acidosis, 2,7 some researches focused on FHR variability analysis. Objective measurement of heart rate variability can be performed with different methods like computerized analysis based on statistical description (i.e., the well-known short-and long-term variabilities), spectral analysis, entropy, and fractal approaches.…”
mentioning
confidence: 99%